Primary Omental Torsion in an Old Woman: Imaging Techniques Can Prevent Unnecessary Surgical Interventions - Mohhamad-Hadi Saeed Modaghegh; Reza Jafarzadeh (Case Reports in Medicine)
Torsion and/or infarction of the greater omentum are rare but well-recognized clinical situations which present as an acute abdomen. The etiology is unknown and speculative. In most cases, the pathology is right sided and clinical presentation consists of an acute or subacute flank pain with mild peritonism usually evoking appendicitis or cholecystitis. Nevertheless, knowledge concerning these two problems can help the surgeon in proper diagnosis and treatment. Since the first report on primary torsion by Eitel in 1899, a few hundred more have been reported and some collective reviews published to date. Recently, ultra sonography and computed tomography have proved to provide sufficiently typical, consistent, and well-recognizable features to avoid unnecessary surgery. In this study, we will present a case diagnosed as primary omental torsion based on computed tomography, which underwent successful conservative management.